THE EFFECT OF INTERNAL COMMUNICATION, RESPONSIBILITY, AND WORK LOYALTY ON EMPLOYEE PERFORMANCE - Riski Ulan Sari; Januar Eky Pambudi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine the influence of Internal Communication, Responsibility, and Loyalty on Employee Performance at Daar-Huda Islamic Boarding School. The sample of this study amounted to 60 respondents with a descriptive approach using quantitative methods, with the help of SPSS software version 26. Sampling using saturated sampling techniques using the entire population as a sample. The results showed that: 1) Internal Communication has a positive and significant effect on Employee Performance. 2) Responsibility has a positive and significant effect on Employee Performance. 3) Work Loyalty has a positive and significant effect on Employee Performance. 4) Internal Communication, Responsibility and Work Loyalty have a positive and significant effect on employee performance. The implications of this study show that Internal Communication, Responsibility and Work Loyalty can improve Employee Performance at Daar El-Huda Islamic Boarding School.